2008
DOI: 10.1007/s12185-008-0067-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolated granulocytic sarcoma of the small intestine successfully treated with chemotherapy and bone marrow transplantation

Abstract: Isolated primary granulocytic sarcoma is a rare disease that presents as an extramedullary tumor of myeloid lineage cells. Most patients subsequently develop acute myelogenous leukemia (AML) within a short period, and their prognosis is poor. Herein, we report the case of a 33-year-old woman with a primary isolated granulocytic sarcoma which originated in the small intestine. After she recovered from surgery, she received intensive chemotherapy equivalent to that for AML, followed by allogeneic bone marrow tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 14 publications
(26 reference statements)
0
26
0
Order By: Relevance
“…2 Several reports have stated that long-term relapse-free survival was achieved in response to allogeneic transplantation. 10,11 However, the graft-versus-leukemia effect, which is a major antitumor effect after allogeneic transplantation, may be less efficient at the extramedullary site when compared with the bone marrow. 12 Several studies have reported that extramedullary relapse occurred after allogeneic transplantation, 13 and extramedullary relapse appeared to be more common after allogeneic transplantation when compared with that after chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…2 Several reports have stated that long-term relapse-free survival was achieved in response to allogeneic transplantation. 10,11 However, the graft-versus-leukemia effect, which is a major antitumor effect after allogeneic transplantation, may be less efficient at the extramedullary site when compared with the bone marrow. 12 Several studies have reported that extramedullary relapse occurred after allogeneic transplantation, 13 and extramedullary relapse appeared to be more common after allogeneic transplantation when compared with that after chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of hematological disorders, 46-75% of patients are initially diagnosed with conditions other than MS; most often, the misdiagnosis is NHL (13,14). During differential diagnosis, it is necessary to also consider poorly differentiated cancers and melanoma, and it children, neuroblastoma, rhabdomyosarcoma, Ewing sarcoma and medulloblastoma (15 (17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Ms Is Likley Underdiagnosed and Thus An Accurrate Prevalencmentioning
confidence: 99%
“…Moreover, 66-88% of patients with an isolated granulocytic sarcoma will develop AML at a mean of 9-11 months after diagnosis (16). Granulocytic sarcoma most commonly occurs in the soft tissues of the skin and bone, soft tissue of the head and neck (frequently the orbits), lymph node; rare cases involve the heart or small intestines and less often in the central nervous system and spinal cord (17)(18)(19). Involvement of the central nervous system (CNS) is rare, and spinal cord compression by granulocytic sarcoma is even more rare (8,9).…”
Section: F I G U R E 3 He Ma T O X Y L I N a N D E O S I N S T A I mentioning
confidence: 99%